Understanding the universe : from quarks to the cosmos - Lincoln, Don (World Scientific, 2004)
The Big Bang, the birth of the universe, was a singular event. All ofthe matter of the universe was concentrated at a single point, withtemperatures so high that even the familiar protons and neutrons ofatoms did not yet exist, but rather were replaced by a swirlingmaelstrom of energy, matter and antimatter. Exotic quarks and leptonsflickered briefly into existence, before merging back into the energysea.